2021
DOI: 10.3991/ijac.v14i2.24085
|View full text |Cite
|
Sign up to set email alerts
|

Switching Gears

Abstract: In March 2020, the COVID-19 pandemic turned into an urgent priority for higher education institutions in that they had to move to remote teaching within a matter of weeks. This paper presents the results of a quantitative survey looking at the challenges university faculty were facing when moving their course(s) online during the first semester of the COVID-19 crisis.The survey looks specifically at course design and formats used in online teaching during the crisis and compares differences occurring between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They found that most challenges were common to both subgroups: technical training, motivation to do work without someone pushing you on your face, and assignment submission and grading difficulties. Moessenlechner et al (2021) presented the results of an online survey with a sample size of 674. They conducted this survey among the whole and part-time faculty at MCI Innsbruck.…”
Section: Introductionmentioning
confidence: 99%
“…They found that most challenges were common to both subgroups: technical training, motivation to do work without someone pushing you on your face, and assignment submission and grading difficulties. Moessenlechner et al (2021) presented the results of an online survey with a sample size of 674. They conducted this survey among the whole and part-time faculty at MCI Innsbruck.…”
Section: Introductionmentioning
confidence: 99%